A comparative study of synthesis and spark plasma sintering of YAG nano powders by different co-precipitation methods. Issue 9 (15th June 2018) - Rahmani, Mahsa; Mirzaee, Omid; Tajally, Mohammad; Loghman-Estarki, Mohammad Reza
Abstract: Pure yttrium-aluminum-garnet (YAG) nano particles were synthesized via normal and reverse co-precipitation methods using nitrate starting solutions and ammonium hydrogen carbonate (AHC) as precipitator agent. The impact of titration method on the phase evolution, thermal behavior, precipitate's composition, morphology and chemical bonds of powders were studied by XRD, TG-DTA, FTIR, FESEM, TEM, EDS and BET analysis. The results revealed that in the normal method, the precipitates were composed of relatively dense particles compared with more homogenous fluffy precipitates with higher carbonate content obtained by the reverse method. The precursors achieved by the reverse method formed less agglomerated and smaller size YAG powders after calcination at 900 °C. Calcined nano powders were processed by spark plasma sintering (SPS) technique at 1350 °C for 10 min without any sintering aids or dispersive agents. The sintering of both powders led to a highly dense and fine submicron-structured YAG ceramic. However, the YAG ceramic produced by SPS of reverse co-precipitated nano powders showed higher transparency (43% at 680 nm and 58% in near-infrared range) and finer micro-structure (about 210 nm in grain size) as compared with normal co-precipitated nano particles.